The Legal Certainty of Notary Deeds in Indonesia Used in Countries Not Joining the Apostille Convention - Rizkawati, Ninda; Arpangi, Arpangi (TABELLIUS: Journal of Law, 2023)
This study aims to find out and analyze legal certainty over the legal status of authentic deeds of Indonesian notaries that are used outside the territory of Indonesia and to find out and analyze the steps that must be taken by notaries so that authentic deeds of notaries in Indonesia can be used outside the territory of Indonesia which not yet a member of the Apostille convention. This research uses Normative Research Methods, with a Conceptual approach and Legislation. The data source used is secondary data in the form of primary, secondary and tertiary legal materials. Data collection techniques using the Library Studies method. With the method of data analysis using Perspective analysis. The results of the study show that: First, the legal status of the Authentic Deeds of Notaries in Indonesia that are applied for through the Legalization process through Diplomatic or Consular channels and the Legalization of Apostille are equally valid. outside the territory of Indonesia that have not joined the Apostille Convention by fulfilling the elements of the validity of an Authentic Deed based on statutory regulations, taking into account the general principles and principles of National Civil Law, National Civil Law of Destination Countries, and International Law. The register Notary specimens at the Directorate General of General Legal Administration, as well as carry out the document legalization process.